Flipped Classroom Learning System Based on Guided Inquiry Using Moodle on Colloid - Lasdina Oktavia Sitanggang; Asra Asra; Mawardi Mawardi (PALAPA, 2022)
This study aims to develop a digital-based learning system so that it can be used to meet the demands of the industrial revolution 4.0 by determining its validity and practicality. The type of research used in this study is Education Design Research (EDR) using the Plomp development model. This research was conducted in one of the public high schools (SMA Negeri 8 Padang) in the 2022/2023 academic year. Data was collected using a validated questionnaire and a practicality questionnaire. The study's results obtained an average validity of 0.87 with a valid category. The results of the practicality test for students have average practicality of 87% in the very practical category and average practicality for teachers of 92% in the very practical category. Overall, from the research results, it can be concluded that the guided inquiry-based flipped classroom learning system using Moodle on colloidal material is valid and practical.